CORRUPTION IN PROCUREMENT OF GOODS AND SERVICES IN MAKASSAR CITY - Matza, Salmawati; Rahmawati, Dian Eka; Nurmandi, Achmad; Suswanta, Suswanta (Journal of Governance and Public Policy, 2020)
The rise of corruption cases in Indonesia at this time every year is always increasing, this causes the community to feel uneasy with corruptors who are still rampant everywhere. The percentage and network of corruption Edy of the supreme court judge?s Decision no.23 /Pid.Sus-TPK/2019/Pn Mks is quite interesting to examine especially if we can see who the dominant actors are in this case, both from the planning process, the bidding process, the bid evaluation process, and implementation and evaluation. This study uses a descriptive qualitative approach which illustrates the phenomenon of Edy corruption case in the supreme court?s decision no.23/Pid.Sus-TPK/ 2019/Pn Mks. Descriptive analysis in this study uses the Nvivo 12 Plus software. Data from this study were sourced from the supreme court decision no.23/Pid.Sus-TPK/2019/Pn Mks and previous research relating to the corruption of edy. the results of this discussion the conclusions that the author can take from the presentation of the analysis above are based on the decision of the supreme court no.23 / Pid.Sus-TPK/2019/Pn Mks analyzed with nvivo12 Plus in general from the four processes above can be seen corporate 44%, Government 52%.